Trends in utilizing CT scan in emergency department: correlation with significant imaging findings and subsequent hospital admissions. A retrospective study - Wazzan, Mohammad; Bakhribah, Ahmad; Abduljabbar, Ahmed; Ahmad, Rani; Alkhatib, Majed; Mansouri, Amr; Khojah, Imad; Addas, Mohammed; Bukhary, Mohammad; Bahubaishi , Khaled; Alshehri, Hassan; Sabri, Mohammad (Journal of King Abdulaziz University: Medical Sciences, 2024)
Introduction: While there is no doubt about the benefits of CT as a diagnostic tool, the associated exposure to ionizing radiation and intravenous contrast along with the financial burden that comes with this modality should be taken into consideration. This study is aimed at evaluating the utilization of head computed tomography (CT) within the emergency department in a Tertiary Hospital. Methods: Data including adult patient demographics, CT utilization and diagnosis, clinical diagnosis and hospital disposition was retrospectively collected using the Electronic Medical Records System (HIS) and the Picture Archiving and Communications System (PACS). Statistical analysis was performed using SPSS IBM. Descriptive statistics were applied. Results: Out of the 2280 scans included, the mean age of the patients was approximately 55 with a standard deviation of 19.36, and with 58.4% of the images done being on male patients. The most frequently scanned body site was the head (1265, 56.8%) with many of those scans (61.9%) turning up negative. Regarding the clinicians’ diagnoses, neurological conditions were the noted causes behind 29.5% of the scans. It should be mentioned that 16.6% of the scans had no clinical diagnoses documented. Contrast was used in 655 (28.7%) of the scans overall, with more than half (54.5%) turning out to be being negative and nearly a fifth of them (19.8%) having no registered clinical diagnoses. Conclusion: Head CT appeared to be the most requested CT scan by the ED. The high proportion of scans with negative findings in addition to the absence of documented clinical diagnosis after doing the scans are concerning factors. Implications for practice: Further investigations into the reason behind these results are recommended to control the unnecessary radiation received by the patients.